2011
DOI: 10.1073/pnas.1110024108
|View full text |Cite
|
Sign up to set email alerts
|

Increased functional connectivity indicates the severity of cognitive impairment in multiple sclerosis

Abstract: Correlations in spontaneous brain activity provide powerful access to large-scale organizational principles of the CNS. However, making inferences about cognitive processes requires a detailed understanding of the link between these couplings and the structural integrity of the CNS. We studied the impact of multiple sclerosis, which leads to the severe disintegration of the central white matter, on functional connectivity patterns in spontaneous cortical activity. Using a data driven approach based on the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
233
7
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 247 publications
(271 citation statements)
references
References 55 publications
27
233
7
1
Order By: Relevance
“…However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012). Such selective increased FC has been reported by several other studies as well (Bonavita et al, 2011;Dogonowski et al, 2013;Hawellek et al, 2011;Richiardi et al, 2012;Rocca et al, 2012;Roosendaal et al, 2010) and has been interpreted as a compensatory mechanism (Bonavita et al, 2011;Roosendaal et al, 2010) because activation studies have shown increased activity in regions devoted to the task and the recruitment of additional regions in MS patients (Pantano et al, 2002;Rocca et al, 2005). It is however also possible that these increases originate from a loss of flexibility in functional interactions, rather than as a compensatory mechanism (Hawellek et al, 2011).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 90%
See 2 more Smart Citations
“…However, we also confirmed the bilateral parahippocampal gyri, right amygdala, left thalamus and left midtemporal pole as more strongly connected in RRMS patients (Richiardi et al, 2012). Such selective increased FC has been reported by several other studies as well (Bonavita et al, 2011;Dogonowski et al, 2013;Hawellek et al, 2011;Richiardi et al, 2012;Rocca et al, 2012;Roosendaal et al, 2010) and has been interpreted as a compensatory mechanism (Bonavita et al, 2011;Roosendaal et al, 2010) because activation studies have shown increased activity in regions devoted to the task and the recruitment of additional regions in MS patients (Pantano et al, 2002;Rocca et al, 2005). It is however also possible that these increases originate from a loss of flexibility in functional interactions, rather than as a compensatory mechanism (Hawellek et al, 2011).…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 90%
“…The importance of these regions suggests that the dynamic FC of at least part of the DMN is altered in patients. These results add to, and complement, several studies which have reported disturbed stationary FC in different parts of the DMN in MS patients (Bonavita et al, 2011;Hawellek et al, 2011;Richiardi et al, 2012;Rocca et al, 2012). The distinction between posterior and anterior/temporal DMN regions seen in eigenconnectivity 6 is similar to the DMN fragmentation observed in Allen et al (in press) and would be missed in conventional stationary FC analyses.…”
Section: Stationary and Dynamic Fc In Rrms Patientssupporting
confidence: 85%
See 1 more Smart Citation
“…Along with the decreased connectivities, these might reflect functional reorganisation to cope with pathological damage, in keeping with results from several imaging studies in MS (Reddy et al, 2000a;Morgen et al, 2004;Mainero et al, 2004;Morgen et al, 2007;Trapp et al, 1998;Hawellek et al, 2011). Compensatory activation is often considered as a process arising at early stages, which tends to be lost with disease progression (Bonavita et al, 2011;Roosendaal et al, 2010).…”
Section: Decreased and Increased Connectivity In Ms Patientssupporting
confidence: 63%
“…Given its complementarity with other diagnostic modalities, future studies should further investigate the sensitivity of this approach for patients with suspected MS or clinically isolated syndromes, and explore its use for monitoring evolution or treatment effects. A particular interest will be the investigation of the link between connectivity alterations and clinically-relevant scales, as interesting links with cognitive performance have been found by other authors (Hawellek et al, 2011). Additionally, spatial relationship between lesion locations and connectivity alterations at the single subject level would be of great interest in order to improve result interpretation with respect to specific attack types.…”
Section: Limitations and Outlookmentioning
confidence: 93%